S. S. North Sea menu, June 19, 1936
This postcard dinner menu is from a Northland Transportation Company passenger liner on the Alaska-Seattle run. An image of S. S. North Sea at Taku Glacier is on the back of the menu. 1 menu; 6 x 9.5 in.